Kinerja Keuangan dalam Restrukturisasi Pembiayaan KPR Saat Covid-19 Pada PT.Bank CIMB Niaga Syariah Medan - Saparuddin Siregar; Nurlaila Nurlaila; Agun Supriyatno (Jurnal Ilmiah Ekonomi Islam, 2022)
Home financing is widely used by people to get the desired housing. During the COVID-19 pandemic, Bank CIMB Niaga Syariah also handled problem financing in the form of financing restructuring for mortgages in accordance with OJK Regulation (Financial Services Authority) Number 11/POJK.03/2020 and Financial Services Authority Regulation Number 40/POJK.03/ 2019. This research was conducted using quantitative methods. The purpose of this study is to explain the financial performance in the restructuring of Bank CIMB Niaga Syariah mortgages before and after the covid-19 pandemic. The results of this study indicate that the calculated F value is 503,490 with sig 0.000, thus it can be concluded that Ho is rejected, or there is a significant difference between financial performance before and after covid-19 and the Anova test on financial performance after covid shows that the calculated F value is 97,284 with sig 0.000, thus it can be concluded that Ho is rejected, or there is a significant difference between financial performance before and after covid-19 at CIMB Niaga Syariah Medan